Enhancing client loyalty of advertising agencies: the influence of creativity and inter-firm relationships - Levin, Elizabeth; Lobo, Antonio; Thaichon, Park (The journal of contemporary issues in business and government, 2016)
This study develops a model for the drivers of loyalty, drawing literature from both service quality and relationship marketing. It investigates how advertising agencies’ creativity and inter-firm relationships influence their clients’ perceived value and overall satisfaction, and in turn how these influence clients’ loyalty towards advertising agencies. A validated survey instrument was used to collect quantitative data. Responses from 119 clients of advertising agencies were analysed using the Partial Least Square (PLS) technique. The model was robust in that inter-firm relationships, overall satisfaction and value followed by creativity explained 72% of variation in loyalty. The findings reveal that the inter-firm relationship is a more important determinant of satisfaction with an advertising agency than creativity, however this relationship is reversed when considering clients’ value perceptions. Service providers such as advertising agencies need to ensure that they focus on all the aspects of service provision to fulfil varying needs and expectations of their clients.